Damages under Malaysian tort law : cases and commentary - Ahangar, Mohd. Altaf Hussain (Sweet & Maxwell Asia, 2009)
Claims in tort are often taken in court with the aim of seeking damages in compensation of the hurt or damage suffered by the claimant. This book analyses and discusses the kinds of damages awarded in various types of tortious claims. Leading cases on damages in the various areas of tort law are commented on to provide critical understanding of the Malaysian jurisprudence on the award of damages under the law of tort. The book is user-friendly. It presents succinct propositions of legal principles under a systematic structure headings. Within each heading, the leading cases are set out together with brief facts and holdings and a concise extract of the judgment of the court. The notes following each case provide commentary, analysis and cross-reference to related materials.